Model of cultural research in the paradigm of theory of systems - P. E. Herchanivska, (Ukrainian Cultural Studies, 2017)
The article is devoted to the development of culturological studies methodological model of the socio-cultural phenomenon based on the theory of systems principles. The analysisis based on a conceptual paradigm: Sociocultural object is a system consisting of separate parts, interconnected by certain relationships; the system is in continuous development and interaction with the external environment. The algorithm of system analysis contains: understanding the basic purpose and functions of the system; the choice of most optimal variant for partitioning system on components (subsystem, elements); introducing of the hierarchy of parts in the structure of the system; detection оf function of each subsystem and linkages between them; definition of the system connections with the environment (or other systems); study of the nature of the variability of the system, of its ability to development and adaptation to the environment. The classification of the sociocultural systems depends on the selected criteria, for example: on the nature of the items, their origin, the variability of propertie, the degree of difficulty, the attitude to the environment, etc. The article reveals the features of system analysis in cultural studies, as well as the potential of the theory of systems in the field of culturology for solving theoretical and practical problems. In the view of the synergetic model, the algorithm of the process of self-organization of the sociocultural system and the mechanisms governing this process are analyzed. The article shows that the self-organization of a sociocultural system is a nonlinear process that is a sequence of phase transitions from an equilibrium state through a nonequilibrium phase and dissipation to bifurcation and relaxation of the system. The process of intercultural interaction is considered through the prism of system analysis. The article shows that the openness of the socio-cultural system is a necessary and indispensable condition for intercultural interaction.
Keywords: theory of systems, system analysis, cultural system, synergetic model, intercultural interaction